A smart flower-like polymeric micelle for pH-triggered anticancer drug release - Oh, Kyung Taek; Oh, Young Taik; Oh, Nam-Muk; Kim, Kwangmyung; Lee, Don Haeng; Lee, Eun Seong (ELSEVIER SCIENCE BV, 2009)
Novel pH-responsive flower-like micelles were developed to provide the mechanism for pH-triggered drug release from drug carriers. The micelles (particle size: similar to 165 nm; critical micelle concentration (CMC): similar to 4 mu g/ml), constructed from poly(N-epsilon-(3-diethylamino)propyl isothiocyanatO-L-lysine)-b-poly(ethylene glycol)-b-poly(L-lactide) [poly(DEAP-Lys)-b-PEG-b-PLLA], were designed to have a self-assembled flower-like arrangement consisting of two hydrophobic blocks [deprotonated poly(DEAP-Lys) block and PLLA block] and a petal-like hydrophilic PEG block at physiological pH. As the pH decreases to slightly acidic pH (<pH 7.0), as in tumor extracellular pH (pH(e)), the flower-like micelles undergo a change in the hydrophobicity of the micellar core. The protonation of poly(DEAP-Lys) changed the physical property of the polymer from hydrophobic to hydrophilic, resulting in disintegration of the micellar core. The co-presence of a pH-insensitive PLLA block in the micellar core affected the protonation of poly(DEAP-Lys), allowing the micelle to be stable at pH 7.0-7.4. In this study using doxorubicin (DOX) as the model drug, DOX release from the micelles accelerated in response to tumor pH(e). (C) 2009 Elsevier B.V. All rights reserved.
Keywords: TUMOR EXTRACELLULAR PH; MACROMOLECULAR THERAPEUTICS; MULTIDRUG-RESISTANCE; CANCER; DELIVERY; NANOTECHNOLOGY; PERMEABILITY; DOXORUBICIN; GLYCOL); OPPORTUNITIES